Leaf structure of Cistus creticus L. (rock rose), a medicinal plant widely used in folk remedies since ancient times - Christodoulakis, N.S.; Georgoudi, M.; Fasseas, C. (Journal of Herbs, Spices and Medicinal Plants, 2014)
The dorsiventral, amphistomatic, hairy, summer and winter leaves of Cistuscreticus had a secretory apparatus in which the secreted resinous material was not preserved in a cutinous wrap, as common during excretion in xerophytes, but was directly spread all over the protective trichomes and the leaf surface. Summer and winter leaves differed in trichome function and density, mesophyll structure, and compactness and secondary metabolite accumulation, mainly phenolics, secreted in excess in the mesophyll cells of the summer leaves. In vitro cell cultures may be used for the production of novel compounds from low-cost precursors. © 2014 Copyright Taylor & Francis Group, LLC.
Keywords: Cistus incanus; Histochemistry; Leaf anatomy; Secondary metabolites; Secreting activity